DNA computing for gastric cancer analysis and functional classification - Chen, Congzhou; Chen, Xin; Li, Xin; Shi, Xiaolong (Frontiers in Genetics, 2022)
Early Identification of key biomarkers of malignant cancer is vital for patients’ prognosis and therapies. There are many researches demonstrated that microRNAs are important biomarkers for cancer analysis. In this article, we used DNA strands Displacement mechanism (DSD) to construct the DNA computing system for cancer analysis. First, gene chips were obtained through bioinformatical training. Those microRNA data and clinic traits are obtained from the Cancer Genome Atlas (TCGA) dataset. Second, we analyzed the Expression data by using weighted gene co-expression network (WGCNA), and found four biomarkers for two clinic features, respectively. Last, we constructed the DSD based DNA computing system for cancer analysis. Inputs of the system are these identified biomarkers, the output is the fluorescent signals that represent their corresponding trait. The experiment and simulation results demonstrated the reliability of the DNA computing system. This DSD simulation system is lab-free but clinically meaningful. We expect this innovative method is useful for rapid and accurate cancer diagnosis.